2020
DOI: 10.1051/parasite/2020005
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Anopheles funestus in malaria transmission in the city of Yaoundé, Cameroon

Abstract: The contribution of Anopheles funestus to malaria transmission in the urban environment is still not well documented. The present study assesses the implication of An. funestus in malaria transmission in two districts, Nsam and Mendong, in the city of Yaoundé. Adult mosquitoes were collected using Centers for Disease Control and Prevention miniature light traps (CDC-LT) and human landing catches from April 2017 to March 2018 and were identified morphologically to the species level. Those belonging to the Anoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…This observation supports regular application of larvicide all year long at least during the first years of the intervention. Analysis of the landscape of the city of Yaounde and transmission risk pattern also indicated a heterogeneous malaria risk with some districts more affected than others 42 , 45 and is in favor for emphasizing larviciding intervention in high risk zone. An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation supports regular application of larvicide all year long at least during the first years of the intervention. Analysis of the landscape of the city of Yaounde and transmission risk pattern also indicated a heterogeneous malaria risk with some districts more affected than others 42 , 45 and is in favor for emphasizing larviciding intervention in high risk zone. An.…”
Section: Discussionmentioning
confidence: 99%
“…The limited impact of larviciding treatments on this species could be due to the fact that these mosquitoes breed in different types of habitats such as pit latrines, which were not specifically targeted during larviciding treatments. It may also be possible that the impact of larviciding treatments in drains which are also preferential breeding habitats for Culex could have been limited due to the presence of solid wastes and many hiding places which could have limited the distribution of larvicide in the water 45 . Culex mosquitoes in Yaounde have also been reported to display a high insecticide resistance profile 46 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The pullulating period of An. funestus is usually observed at the end of the rainy season and up to the middle of the dry season [ 38 , 39 ] while, in contrast, An. gambiae ( s.l. )…”
Section: Discussionmentioning
confidence: 99%
“…These gures are consistent with previous ndings 47,48 . Although studies conducted so far in Yaoundé suggested seasonal malaria transmission pattern 35,37,39 , it is possible that transmission could be occurring at an undetectable rate in some period of the year due to the permanent presence of An. gambiae sl in the city and gametocyte carriers.…”
Section: Discussionmentioning
confidence: 97%